How latitudes become forms : art in a global age. - Allora, Jennifer; Altay, Can; Appadurai, Arjun; Arima, Kaoru; Atelier Bow-Wow; Atkinson, Christi; Bahri Alptekin, Hüseyin; Belting, Hans; Bierinckx, Cis; Bither, Philip; Broeckmann, Andreas; Cabelo; et al. (Minneapolis : Walker Art Center Minneapolis, 2003)
Allora & Calzadilla ; Altay, Can ; Arima, Kaoru ; Atelier Bow-Wow ; Bahri Alptekin, Hüseyin ; Cabelo ; Cassaro, Franklin ; Cucullu, Santiago ; Dube, Anita ; Ersen, Esra ; Gowda, Sheela ; Ito Zon ; Jamie, Cameron ; Karamustafa, Gülsün ; Langa, Moshekwa ; Liang, Zhao ; Marepe ; Oki, Hiroyuki ; Ozawa Tsuyoshi ; Raqs Media Collective ; Rhode, Robin ; Seejarim, Usha ; Shettar, Ranjani ; Song Dong ; Tabaimo ; Wang Jianwei ; Yin Xiuzhen
To invite and encourage such dialogue, How latitudes become forms : art in a global age looks at current scholarship on globalism and changing curatorial practices, and identifies critical models provided by artists themselves. This catalogue features thought-provoking essays and conversations by curators, critics, and cultural programmers from across the world as well as the multidisciplinary artworks of more than forty visual, film / video, performing and new media artists from Brazil, China, India, Japan, South Africa, Turkey, and the United States.
How latitude become forms : art in a global age, Contemporary Arts Museum, Houston, Fondazione Sandretto Re Rebaudengo per l'Arte, Torino, Walker Art Center, Minneapolis, 2003-02-09. 2003-06-05, 2004-07-17. 2003-05-04, 2003-09-14. 2004-10-03
boek